Inflation hedging characteristics of Malaysian residential property: 1997-2006 / Normizawati Kamarulzaman - Kamarulzaman, Normizawati (2007)
The purpose of this research is to assess the role of inflation rate towards the residential property prices. The study setting is taken from the year 1997 until 2006 and the data will be made on the quarterly basis shows that residential property in Malaysia is affected by the inflation rate, interest rate and gross national income which is found on the previous study that the property is around 20 percent prone (80 percent inflation proof). As for the methodology, the dependent variable of this study is the residential property prices which can be measured by the Malaysian Housing Price Index (MHPI) while the independent variables are the inflation rate which can be measured by the Consumer Price Index (CPI), interest rates represented by the Base Lending Rate (BLR) and the economic growth measured by Gross National Income (GNI). All the data will be collected through secondary sources such as annual reports, Department of Statistics, Bank Negara Malaysia, and some from the DataStream facility. For the data analysis, this study will use the Multiple Linear Regression and Correlation as the statistical tools to run the test in looking for the results.